1966
DOI: 10.1002/aic.690120129
|View full text |Cite
|
Sign up to set email alerts
|

The finite‐difference computation of natural convection in a rectangular enclosure

Abstract: A study is made of the natural convection of a fluid contained in a long horizontal enclosure of rectangular cross section with one vertical wall heated and the other cooled. Two‐dimensional motion is assumed. The governing vorticity and energy transport equations are solved by an implicit alternating direction finite‐difference method. Transient and steady state isothermals and streamlines are obtained for Grashof numbers up to 100,000 and for height‐to‐width ratios of 1, 2, and 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
5

Year Published

1967
1967
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(62 citation statements)
references
References 11 publications
3
54
0
5
Order By: Relevance
“…This method, however, was apparently handicapped by the lack of a continuous recording technique. (9,34,43) for laminar free convection in a vertical axisymmetric enclosure with a small heated spot centrally located on the floor. He concluded that the calculated flows for all methods were similar and the required computer times were also of comparable magnitudes.…”
Section: Scope Of This Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This method, however, was apparently handicapped by the lack of a continuous recording technique. (9,34,43) for laminar free convection in a vertical axisymmetric enclosure with a small heated spot centrally located on the floor. He concluded that the calculated flows for all methods were similar and the required computer times were also of comparable magnitudes.…”
Section: Scope Of This Workmentioning
confidence: 99%
“…An equation similar to (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) may be obtained 152 I m, 2 from the principle of conservation of mass. This may be used to chec the results of Equation (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The early investigations in this area include Ostrach [1], Wilkes and Churchill [2], and de Vahl Davis [3] who introduced a numerical solution for 2-D natural convection in a rectangular cavity. A large number of other studies followed examining a variety of cavities.…”
Section: Introductionmentioning
confidence: 99%